Trace Element Carrier Phases at Micron-Scale in Allende Matrix and Chondrules - Bland, Philip; Cleverley, J.; Dyl, Kathryn; Hough, R.; Fisher, L.; Ryan, C. (Lunar and Planetary Science Institute, 2012)
We have used Synchrotron XRF to do large-area trace element mapping of whole thin sections. These data reveal the exceptional mineralogical and compositional heterogeneity of chondritic material at the µm-scale.